2020
DOI: 10.3390/diagnostics10060392
|View full text |Cite
|
Sign up to set email alerts
|

State-of-the-Art Technology of Model Organisms for Current Human Medicine

Abstract: Since the 1980s, molecular biology has been used to investigate medical field mechanisms that still require the use of crude biological materials in order to achieve their necessary goals. Transcription factor-induced pluripotent stem cells are used in regenerative medicine to screen drugs and to support lost tissues. However, these cells insufficiently reconstruct whole organs and require various intact cells, such as damaged livers and diabetic pancreases. For efficient gene transfer in medical use, virally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…The impact made on IEM by the zebrafish model is evident. Even more, the influence zebrafish studies had in the last decades in a great variety of diseases and their relevance for human treatment has been highlighted in numerous publications [ 159 , 192 , 193 , 194 , 195 , 196 , 197 ]. It is to be expected that the role of zebrafish will continue to grow for rare metabolic disorders, especially with the prospect of drug screening and the effectiveness of CRISPR/Cas9 editing.…”
Section: Discussionmentioning
confidence: 99%
“…The impact made on IEM by the zebrafish model is evident. Even more, the influence zebrafish studies had in the last decades in a great variety of diseases and their relevance for human treatment has been highlighted in numerous publications [ 159 , 192 , 193 , 194 , 195 , 196 , 197 ]. It is to be expected that the role of zebrafish will continue to grow for rare metabolic disorders, especially with the prospect of drug screening and the effectiveness of CRISPR/Cas9 editing.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, animal models, including nematodes, are used for basic studies for medical applications, such as mechanism studies and drug discovery, as summarized in [32]. Here, we focused on another application to study the tumor microenvironment using C. elegans.…”
Section: Innovative Methods For Studying the Tumor Microenvironmentmentioning
confidence: 99%
“…It is common knowledge that some animals have sensory abilities superior to those of humans, such as smelling, and animal use will fill the gap in achieving detection of phenomena via smelling [32]. In a study by Lo et al, memory tests of Canis familiaris, Rattus norvegicus, and Homo sapiens indicated that dogs were superior to rats and that dogs and rats were superior to humans [33].…”
Section: Smell Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…C. elegans shows avoidance of the urine of healthy individuals while displaying a chemotactic attraction toward the urine of patients with 15 types of cancer (stomach, colon-rectum, lung, breast, pancreas, liver, prostate, uterus, esophagus, gallbladder, bile duct, kidney, urinary bladder, ovary, oropharynx) rendering N-NOSE a primary multi-cancer screening test [ 20 , 24 , 25 , 30 , 31 ]. N-NOSE clinical studies with human patients from cancer stages 0 to Ⅳ have highlighted the good performance at early detection (stages 0-Ⅰ) without lymphatic metastasis, in addition to detecting advanced stages [ 20 , 24 , 25 , 30 , 31 ]. This test only requires ≥1 mL of urine, which is non-invasive, painless, and stress-free for the subject [ 20 , 28 ].…”
Section: Introductionmentioning
confidence: 99%